Community Engagement for Student Faith Development: Service-Learning in the Pentecostal Tradition. Issue 1 (1st January 2020) - Dirksen, Carolyn
Abstract: Community engagement through service-learning has been a mainstay of higher education for the past 20 years and has increasingly proven successful in grounding academic knowledge in community experience. This article explores how service-learning programs designed to shape students' sense of responsibility for the common good can also foster their faith development. In particular, it examines natural connections between service-learning and the Pentecostal tradition, and details how service-learning has been implemented at Lee University (located in Cleveland, Tennessee, USA) by drawing upon the institution's theological heritage and using Sharon Daloz Parks's theory of faith development. Three tensions encountered when implementing the program are explored: the assumption that academic learning is separate from and superior to affective learning, the concept that all service should be oriented ultimately toward evangelism, and the notion of the "savior" motivation that nullifies the cultural humility necessary for personal transformation. The article concludes by offering a series of lessons learned regarding the implementation of community engagement programs as a learning strategy within the Christian college context.